2000
DOI: 10.1103/physrevlett.84.3666
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Phase-Separated Quantum Dots in Cubic InGaN Layers from Resonant Raman Scattering

Abstract: The emission of light in the blue-green region from cubic InxGa1-xN alloys grown by molecular beam epitaxy is observed at room temperature and 30 K. By using selective resonant Raman spectroscopy (RRS) we demonstrate that the emission is due to quantum confinement effects taking place in phase-separated In-rich quantum dots formed in the layers. RRS data show that the In content of the dots fluctuates across the volume of the layers. We find that dot size and alloy fluctuation determine the emission wavelength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
64
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 101 publications
(68 citation statements)
references
References 20 publications
4
64
0
Order By: Relevance
“…Work by Kehagias et al [9] has used EDX mapping to show that InGaN nanorods grown on (111)-Si substrates have increasing In composition along the length of nanorods which is due to high In desorption rates at temperatures of 450°C. In segregation has also been reported in quantum well and quantum dot structures [4] and in other alloy systems such as InGaAs [10].…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Work by Kehagias et al [9] has used EDX mapping to show that InGaN nanorods grown on (111)-Si substrates have increasing In composition along the length of nanorods which is due to high In desorption rates at temperatures of 450°C. In segregation has also been reported in quantum well and quantum dot structures [4] and in other alloy systems such as InGaAs [10].…”
mentioning
confidence: 97%
“…This spans the visible spectrum and makes InGaN a viable candidate for optoelectronic devices such as LEDs, lasers and photovoltaics [1,2]. Growth of InGaN may be achieved using various growth techniques such as molecular beam epitaxy (MBE) [3,4], pulsed laser deposition [5] and metal-organic chemical vapour deposition [2,6,7]. However due to a lack of adequately lattice matched substrates InGaN films generally have high threading dislocations.…”
mentioning
confidence: 99%
“…1 However, there is strong evidence that an important emission mechanism originates from phase-separated quantum dots ͑QDs͒ formed by spinodal decomposition taking place in the InGaN alloys, the active media in these devices. [2][3][4] Spinodal decomposition occurs below a critical temperature and for a range of the alloy composition which defines a miscibility gap at a given temperature. It has been recognized from theory for a long time that the critical temperature lowers significantly due to biaxial strain in coherently grown semiconductor epitaxial layers and the miscibility gap may even be suppressed.…”
mentioning
confidence: 99%
“…6,[20][21][22][23][24][25] It has been found that the internal quantum efficiency can be enhanced by nanoscale islands or quantum dots observed in AlGaN. 6,20,24 Moreover, atomic-scale compositional superlattice (SL) has also been observed in Al-rich AlGaN thin films grown by molecular-beam epitaxy.…”
Section: Introductionmentioning
confidence: 99%